Super selective arterial embolization to treat radiation-induced hemorrhagic gastritis: a case report and review of the literature. (2nd January 2021) - Mossa, Michelangela; Neri, Benedetto; Scarozza, Patrizio; Del Vecchio Blanco, Giovanna; Giannelli, Mario; Argirò, Renato; Di Carlo, Sara; Monteleone, Giovanni; Petruzziello, Carmelina
Abstract: Radiation-induced hemorrhagic gastritis (RIHG) is a rare but potentially fatal event following radiotherapy for locally advanced gastric cancer; the treatment of this condition is not standardized. Only few cases of RIHG have been reported, treated with different therapeutic approaches. Here we report the case of a 79-year-old patient who underwent subtotal gastrectomy for gastric cancer, followed by adjuvant chemo-radiotherapy. Approximately 3 months after the end of the treatment, she developed recurrent diffuse bleeding originating from the entire mucosa of the gastric pouch and from a marginal ulcer. As the bleeding was refractory to several endoscopic treatments and surgery was not indicated, the patient underwent two sessions of transcatheter selective arterial embolization, with resolution of bleeding. Arterial embolization has already been reported for the treatment of hemorrhagic cystitis, developing after irradiation of the pelvis for prostate, bladder, rectum, and cervix cancer. However, to our knowledge, it has never been reported as a treatment for hemorrhagic gastritis. Based on this case, we suggest arterial embolization as an option in the management of RIHG, when standard endoscopic treatment fails.